2021
DOI: 10.1098/rsos.210225
|View full text |Cite
|
Sign up to set email alerts
|

Buoys with looming eyes deter seaducks and could potentially reduce seabird bycatch in gillnets

Abstract: Bycatch of seabirds in gillnet fisheries is a global conservation issue with an estimated 400 000 seabirds killed each year. To date, no underwater deterrents trialled have consistently reduced seabird bycatch across operational fisheries. Using a combination of insights from land-based strategies, seabirds' diving behaviours and their cognitive abilities, we developed a floating device exploring the effect of large eyespots and looming movement to prevent vulnerable seabirds from diving into gillnets. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Acoustic pulses have been used to deter marine mammals (Waples et al 2013) and may hold promise for seabirds in some situations (Melvin et al 1999;McGrew 2019). However, a recent study found that buoys with painted "googly" eyes deterred sea ducks from certain spaces (Rouxel et al 2021); this may be a practical means of deterrence of loons and sea ducks. Finally, shifting the timing of the fishery may hold promise for reducing loon and other seabird bycatch in Arctic gill-net fisheries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic pulses have been used to deter marine mammals (Waples et al 2013) and may hold promise for seabirds in some situations (Melvin et al 1999;McGrew 2019). However, a recent study found that buoys with painted "googly" eyes deterred sea ducks from certain spaces (Rouxel et al 2021); this may be a practical means of deterrence of loons and sea ducks. Finally, shifting the timing of the fishery may hold promise for reducing loon and other seabird bycatch in Arctic gill-net fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study found that buoys with painted “googly” eyes deterred sea ducks from certain spaces (Rouxel et al. 2021); this may be a practical means of deterrence of loons and sea ducks. Finally, shifting the timing of the fishery may hold promise for reducing loon and other seabird bycatch in Arctic gill‐net fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…In the same area, Bielli et al (2020) reported an 84% reduction in seabird bycatch using green LEDs, although statistical significance was not reported. Looming eye buoys (rotating panels with eye spots, attached to a buoy) are a promising development in deterring seabirds, with significant reductions of long-tailed duck abundance within 50 m of the modified buoys compared to controls (Rouxel et al 2021).…”
Section: Visualmentioning
confidence: 99%
“…In this study, habituation trials were confounded by the seasonal presence of migrating ducks, so further research was suggested to investigate the long-term deterrent capabilities of looming eye buoys (Rouxel et al 2021).…”
Section: Visualmentioning
confidence: 99%
See 1 more Smart Citation